A primer on damages of cartel suppliers: Determinants, standing US vs. EU and econometric estimation - Eckart Bueren; Florian Smuda (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2013)
While private actions for damages by customers against price-cartels receive much attention, the treatment of other groups affected by such conspiracies is largely unresolved. This article narrows the research gap with respect to suppliers to a downstream price cartel. First, we show that such suppliers incur losses driven by a direct quantity, a price and a cost effect. We then analyze whether suppliers are entitled to claim these losses as damages in the two leading competition law regimes. We find that, while the majority view in the US denies standing, the emerging position in the EU and important member states is to grant supplier standing. We argue that this can indeed be justified in view of the different institutional context and the goals assigned to the right to damages in the EU. We finally present an econometric approach based on residual demand estimation that allows to quantify all determinants of cartel suppliers' damages, thereby showing that supplier damage claims are a viable option in practice that can contribute to full compensation and greater cartel deterrence.
urn:nbn:de:bsz:180-madoc-346812; Older version: http://hdl.handle.net/10419/80717; More recent version: http://hdl.handle.net/10419/106512
Keywords: L41; K21; 330; competition policy; cartels; suppliers; damage quantification; standing; private enforcement; comparative law